2022
DOI: 10.3389/fcvm.2022.951597
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for Forkhead box transcription factors in diabetic cardiomyopathy: Their therapeutic potential and possible effects of salvianolic acids

Abstract: Diabetic cardiomyopathy (DCM) is the primary cause of morbidity and mortality in diabetic cardiovascular complications, which initially manifests as cardiac hypertrophy, myocardial fibrosis, dysfunctional remodeling, and diastolic dysfunction, followed by systolic dysfunction, and eventually end with acute heart failure. Molecular mechanisms underlying these pathological changes in diabetic hearts are complicated and multifactorial, including but not limited to insulin resistance, oxidative stress, lipotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…Its main function is to improve the viscous state of blood, with blood circulation, blood stasis, and good clinical tolerance ( 385 , 386 ). Current studies have shown that its mechanism of action is to inhibit the inflammatory response of endothelial cells, improve energy metabolism, promote vascular endothelial cell migration, and improve ischemia-reperfusion injury ( 380 , 387 , 388 ). Studies have shown that salvianolic acid can reduce the inflammatory factors (such as ICAM-1, IL-1β, IL-18 and TNF-α) in the cerebral cortex of the rat brain MCAO/R model, and reduce the apoptosis of cortical neurons.…”
Section: Modulatory Effects Of Natural Botanical Components On Microg...mentioning
confidence: 99%
“…Its main function is to improve the viscous state of blood, with blood circulation, blood stasis, and good clinical tolerance ( 385 , 386 ). Current studies have shown that its mechanism of action is to inhibit the inflammatory response of endothelial cells, improve energy metabolism, promote vascular endothelial cell migration, and improve ischemia-reperfusion injury ( 380 , 387 , 388 ). Studies have shown that salvianolic acid can reduce the inflammatory factors (such as ICAM-1, IL-1β, IL-18 and TNF-α) in the cerebral cortex of the rat brain MCAO/R model, and reduce the apoptosis of cortical neurons.…”
Section: Modulatory Effects Of Natural Botanical Components On Microg...mentioning
confidence: 99%
“…In addition to miR-182, miR-24-3p and miR-21-5p can be delivered by HUCMSC-EXOs and shift the polarization M1 macrophages to the M2 phenotype, not only suppressing the inflammatory response but also promoting the repair of diseased myocardial tissue [ 44 , 94 ]. Forkhead box protein O1 (FOXO1) is highly expressed in myocardial tissue and is closely associated with inflammatory signaling-related pathways [ 95 ]. BMSC-EXOs overexpressing miR-183-5p were recently shown to alleviate MIRI by downregulating FOXO1 expression [ 39 ].…”
Section: Msc-exo-derived Ncrnas In Mirimentioning
confidence: 99%
“…A recent study reported that FOXO signaling pathway was enriched and activated in DN [ 22 ]. The acetylation of FOXO family was also demonstrated to be related with the progression of diabetic cardiomyopathy [ 23 ]. Nevertheless, the impact of Apelin on the FOXO signaling pathway remains unclear and requires further investigation.…”
Section: Introductionmentioning
confidence: 99%